Detailed study and evaluation of the oil potential from the Guadalupe formation:an oil field in Arauca, Colombia (2017)
The search for new reservoirs and, therefore, new oil reserves is one of the key challenges in the oil and gas industry. The current scenario of many fields in Colombia is a high development and a notable depletion of its reservoirs. Company Z, which has operations in a major field of the Llanos Basin, recently discovered Field L and is producing from the, corporately named, reservoirs M1, M2, M3 and K2. Summing up an Original Oil in Place (OOIP) of 50 MMBO for this new field. Due to its young production history and to the lack of knowledge in the oil accumulation within the reservoirs, there is an underestimation of the potential of undeveloped Cretaceous K1 unit (Guadalupe Formation). This study suggests that there is a high potential in the three most prospective sandstones of K1 unit and that there is a possibility of having an additional 60% of the original OOIP. Additional to that, a potential map determines where is the best location and a decision tree will help the company in making the appropriate choices